PENGARUH PEMBERIAN VITAMIN C DAN E TERHADAP GAMBARAN HISTOLOGIS HEPAR MENCIT (Mus musculus L.) YANG DIPAJANKAN MONOSODIUM GLUTAMAT (MSG) - Ahri Maulida; Syafruddin Ilyas; Salomo Hutahaean (Saintia Biologi, 2013)
This study aimed to determine the effects of vitamin C and E on liver microstructure of mouse exposed to monosodium glutamate (MSG) for 30 days. The experiment used completely randomized design which consists of 6 treatments and  5 replications. Mice were treated daily by oral gavage with 4 mg MSG (P1),  4 mg MSG + 0.26 mg  vitamin C (P2),  4 mg MSG + 0.026 vitamin E (P3), or  4 mg  MSG + 0.26 mg  vitamin C + 0.026 mg vitamin E (P4). All dosages were based on mg/g body weight. Two control groups K- and K+ were treated with water and castor oil respectively. The mice liver tissue slide was prepared by the paraffin method and stained with haematoxylin-eosin (HE). The results showed that MSG caused cell degeneration and necrosis in liver tissue. Vitamin C and E was  able to recover  liver cell damage induced by MSG.  The highest result was found in P3 and combination treatment (P4) where the recovery effect reaches 64% and 80% respectively. Keywords : Liver, Monosodium glutamate (MSG), Vitamin C, Vitamin E.